An anti-OX40 antibody to treat moderate-to-severe atopic dermatitis: a multicentre, double-blind, placebo-controlled phase 2b study. Issue 10372 (21st January 2023) - Guttman-Yassky, Emma; Simpson, Eric L; Reich, Kristian; Kabashima, Kenji; Igawa, Ken; Suzuki, Tetsuya; Mano, Hirotaka; Matsui, Takeshi; Esfandiari, Ehsanollah; Furue, Masutaka
Summary: Background: OX40 is crucial for T-cell differentiation and memory induction. The anti-OX40 antibody, rocatinlimab inhibits the OX40 pathway. We evaluated the efficacy and safety of rocatinlimab in adults with moderate-to-severe atopic dermatitis. Methods: This multicentre, double-blind, placebo-controlled phase 2b study was done at 65 secondary and tertiary sites in the USA, Canada, Japan, and Germany. Eligible patients were adults (aged 18 years or older) with confirmed atopic dermatitis (American Academy of Dermatology Consensus Criteria or local diagnostic criteria) with moderate-to-severe disease activity, as defined by an Eczema Area and Severity Index (EASI) score of 16 or more, validated Investigator's Global Assessment for Atopic Dermatitis score of 3 (moderate) or 4 (severe), and affected body surface area 10% or higher at both screening and baseline, with documented history (within 1 year) of inadequate response to topical medications or if topical treatments were medically inadvisable. Patients were randomly assigned (1:1:1:1:1) to receive subcutaneous rocatinlimab every 4 weeks (150 mg or 600 mg) or every 2 weeks (300 mg or 600 mg) or subcutaneous placebo up to week 18, with an 18-week active-treatment extension and 20-week follow-up. Percentage change from baseline in EASI score was assessed as the primary endpoint at week 16 and during the active extension and follow-up in all randomly assigned patients exposed to study drug with a post-baseline EASI score at week 16 or earlier according to the group they were randomly assigned to. Safety was assessed in all randomly assigned patients exposed to study drug; patients were analysed according to the group they were randomly assigned to. The study is registered with ClinicalTrials.gov, NCT03703102 . Findings: Between Oct 22, 2018, and Oct 21, 2019, 274 patients (114 [42%] women, 160 [58%] men; mean age 38·0 years [SD 14·5]) were randomly assigned to one of the rocatinlimab groups (217 [79%] patients) or to the placebo group (57 [21%] patients). Compared with placebo (−15·0 [95% CI −28·6 to −1·4]), significant least-squares mean percent reductions in EASI score at week 16 were observed in all rocatinlimab groups (rocatinlimab 150 mg every 4 weeks −48·3 [−62·2 to −34·0], p=0·0003; rocatinlimab 600 mg every 4 weeks −49·7 [−64·3 to −35·2], p=0·0002; rocatinlimab 300 mg every 2 weeks −61·1 [−75·2 to −47·0], p<0·0001; and rocatinlimab 600 mg every 2 weeks −57·4 [−71·3 to −43·4], p<0·0001). The most common adverse events during the double-blind period in patients receiving rocatinlimab (adverse events ≥5% of patients in the total rocatinlimab group and more common than the placebo group) were pyrexia (36 [17%] patients), nasopharyngitis (30 [14%] patients), chills (24 [11%] patients), headache (19 [9%] patients), aphthous ulcer (15 [7%] patients), and nausea (13 [6%] patients). There were no deaths. Interpretation: Patients treated with rocatinlimab had progressive improvements in atopic dermatitis, which was maintained in most patients after treatment discontinuation. Treatment was well tolerated. Funding: Kyowa Kirin.